Detection and Characterization of the Metabolites of Ciwujianoside B in Rats Based on UPLC-Fusion Lumos Orbitrap Mass Spectrometry - Wan-Ru Dong; Xue Gao; Chen-Xue Li; Yan Song; Jun-Hong Chai; Jun Liang (Journal of Analytical Methods in Chemistry)
We previously conducted a systematic study on the metabolic process and products of hederasaponin B in rats. We hypothesized that the sugar chain structures play a key role in the metabolism of triterpenoid saponins. To verify this hypothesis, we conducted metabolic research on ciwujianoside B ascribed to the same sugar chains and a distinct aglycone and compared it with hederasaponin B. Specifically, we collected feces, urine, and plasma of rats after gavage with ciwujianoside B and identified 42 metabolites by UPLC-Fusion Lumos Orbitrap mass spectrometry. Finally, ciwujianoside B metabolism and hederasaponin B metabolism were compared, reaching the following conclusions: (i) more than 40 metabolites were identified in both, with the majority of metabolites identified in feces; (ii) the corresponding metabolic pathways in vivo were basically similar, including deglycosylation, acetylation, hydroxylation, glucuronidation, oxidation, and glycosylation; and (iii) deglycosylation was considered the main metabolic reaction, and its metabolites accounted for approximately 50% of all metabolites. Overall, this study provides a foundation for further research on the metabolism of triterpenoid saponins.